Industrial training report: Bosch Power Tools Sdn Bhd Malaysia / Nurhidayati Atikah Anuar - Anuar, Nurhidayati Atikah (Universiti Teknologi MARA, Perlis, 2023)
Chasing technological innovation is extremely challenging when it comes to doing business, particularly in the manufacturing industry. This is because the globe or market may expand quickly, people's behaviors may shift, and the economy or environment may change. The German company Bosch is a market leader on a worldwide scale and is wellknown for the high-quality goods it manufactures, as well as its emphasis on developing environmentally and socially responsible solutions. They provide a wide range of interests that may be found in one of their four business segments: Consumer goods, Industrial Technology, Mobility Solutions, and Energy and Building Technology. Since I am a new intern in the purchasing division at Bosch Power Tools Sdn Malaysia, one of my responsibilities is to acquire knowledge about Bosch so that I can help them reach their objectives. The training program covers various areas of product buying, including coordination with relevant suppliers, acquiring samples and completing testing, and coordinating with other subsidiaries to guarantee efficient management of new sample purchases, among other topics. The buyer for the project plays an essential part in coordinating new project needs with the providers most suited to satisfy those requirements. This industrial research includes a company profile, training reflection, and SWOT analysis of Bosch, which might identify Bosch as a company that Invented for Life. The strengths, weaknesses, opportunities, and threats are all outlined in this analysis.